Pengaruh Debt to Equity Ratio dan Intellectual Capital Terhadap Profitabilitas dengan Pertumbuhan Laba Sebagai Variabel Intervening - Rahmi Atul Ahda; Fitri Yeni; Agam Mei Yudha (Economic Reviews Journal, 2024)
With profit growth as an intervening variable, these findings try to understand how the DER ratio and Intellectual capital influence the profitability of several manufacturing companies, namely manufacturing companies listed on the IDX. Aquantitative approach was used to find these findings. The research population was 214 manufacturing companies on the BEI between 2018 and 2022. During the five year research period, a sample of 56 manufacturing companies was obtained by applying the purposivesampling method which was used to determine which samples met the specified requirements. The technique used to see the results of these findings is to investigate a more precise panel data regression using SPSS 25. The findings show that the DER ratio has a positive and insignificant influence on profit growth, Intellectual capital has a negative and significant influence on profit growth, DER hasa negative and insignificant influence on profitability, Intellectual capital has a positive and significant influence on profitability, profit growth has a negative ang insignificant influence on profitability, and prifitgrowth is unable to mediate between DER and Intellectual capital on Profitability.